Frequência de alergia ao látex tipo I em trabalhadores expostos do Hospital de Clínicas de Uberlândia, da Universidade Federal de Uberlândia - Fernandes, Cristiane (2015)
In despite of type I latex allergy being well documented, it is not yet under controll. It is an object of interest for different medicine departments by the pottencial risk of severe reactions and the lack of diagnostics exams. The aims of this study were to identify the frequency of latex allergy type I, the factors associated with this and search for predictors of a positivity of specific latex Immunoglobulin E (IgE) antibody. It was a cross-sectional study of three hundred ninety health workers at Hospital de Clínicas de Uberlândia da Universidade Federal de Uberlândia- HCU-UFU. The assessment was from February to October 2013, after the received approval from the Research Ethics Committee of the Universidade Federal de Uberlândia (CEP). It was applicated a questionnaire for all the participants, and those who had symptoms to latex were obtained serum samples for test of specific IgE antibody to latex by immunocap assay. The questionnaire had variables sociodemographic including work activities, associated factors and symptoms. The healthworkers were separated according to clinical history: symptomatics and assymptomatics to latex. In the symptomatic group was dominant: the female gender, history of allergic reactions, use of antiallergic drugs and number of previous surgeries. The symptomatics were then classified according to the results of specific IgE to latex in positive and negative groups. Years of work in the health system, number of hours wearing gloves, job title and department did not show risk factors. The most related symptoms were hands and itchy nose. Between IgE positive and IgE negative groups the Spearman test (RS) and odds ratio (OR) was significant for the sum of hand symptoms equal 6 and for the sum of systemic symptoms equal 7, and for frequency of symptoms mostly diary. This study concluded that the number of symptoms, for hands or systemic, hereafter the frequency of them could be predictors of a positivity result to specific latex IgE antibody test. It is probable that false negatives occurred in the symptomatic group because of a limitation of sensibility of the test. This supports the need for improvement in diagnostic tests for this disease. The use of questionnaire could be useful in screening health workers with low cost.